2023
DOI: 10.1111/acel.13786
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum supplementation improves age‐related delays in fracture repair

Abstract: Age‐related delays in bone repair remains an important clinical issue that can prolong pain and suffering. It is now well established that inflammation increases with aging and that this exacerbated inflammatory response can influence skeletal regeneration. Recently, simple dietary supplementation with beneficial probiotic bacteria has been shown to influence fracture repair in young mice. However, the contribution of the gut microbiota to age‐related impairments in fracture healing remains unknown. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 113 publications
0
12
0
Order By: Relevance
“…They also noted decreased IL-6 levels in the treatment group, in contrast to our observation of an increase in IL-6. In a subsequent study, the same group found similar results in aged mice, although again only probiotic treatment pre-fracture was investigated [ 22 ].…”
Section: Discussionmentioning
confidence: 88%
“…They also noted decreased IL-6 levels in the treatment group, in contrast to our observation of an increase in IL-6. In a subsequent study, the same group found similar results in aged mice, although again only probiotic treatment pre-fracture was investigated [ 22 ].…”
Section: Discussionmentioning
confidence: 88%
“…The evidence for the beneficial effects of probiotics initially came from studies on fracture healing and osteoporosis treatment, indicating their systemic effects. Numerous animal and human studies have found that the administration of various probiotic strains, such as Lactobacillaceae and Bifidobacterium species, can accelerate fracture healing, promote osteogenic differentiation, and improve bone trabecular parameters [ 59 , 60 , 61 , 62 ]. It has been suggested in the literature that supplementation with specific strains of Bifidobacterium , particularly in the elderly population, can expedite fracture repair [ 62 ].…”
Section: The Role Of Probiotics In Bone Regeneration and Bone Homeost...mentioning
confidence: 99%
“…Numerous animal and human studies have found that the administration of various probiotic strains, such as Lactobacillaceae and Bifidobacterium species, can accelerate fracture healing, promote osteogenic differentiation, and improve bone trabecular parameters [ 59 , 60 , 61 , 62 ]. It has been suggested in the literature that supplementation with specific strains of Bifidobacterium , particularly in the elderly population, can expedite fracture repair [ 62 ]. In models of osteoporosis induced by various factors, administration of probiotics such as Lactobacillaceae and Bifidobacterium has been shown to increase bone density, attenuate bone loss, and maintain bone homeostasis [ 56 , 61 , 63 , 64 , 65 , 66 ].…”
Section: The Role Of Probiotics In Bone Regeneration and Bone Homeost...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, supplementing a single strain of B. longum accelerated the formation of callus, thereby improving the mechanical performance of fractured limbs and promoting bone fracture repair in 18-month-old female mice. 10 B. longum UBBL-64 significantly enhanced bone mass and strength in osteoporotic mice, regulated the ratio of immune cells in lymphocytes, and improved bone microstructure. 11 B. longum 35624® inhibited osteoclast formation through the production of extracellular polysaccharides, thereby activating the TLR2-dependent pathway.…”
Section: Introductionmentioning
confidence: 96%